New triple-mode high-amplitude Delta Scuti variables - Khruslov Anton V. (Open Astronomy, 2022)
I present a detection of four new triple-mode high-amplitude Delta Scuti variables, pulsating in the fundamental, first, and second overtone modes. This is a new addition to the ten known cases in the Galaxy. I used the data of ASAS-SN and analyzed them using the WinEfk code by V. P. Goranskij. Light elements and parameters of the light curves were obtained.